Impact of remote learning during the Covid-19 lockdown on Roma pupils in Slovenia - Bešter, Romana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The article analyses the impact of remote learning during the Covid-19 lockdown on Roma pupils in Slovenia. Roma are one of the most marginalised and vulnerable groups in Slovenia. Most of them record poor inclusion and performance in education, which is why the suspension of regular school activities is likely to have much broader negative consequences for these pupils. Based on the outcomes of the study that included surveys among Roma assistants and teachers, the article analyses the technical conditions available to Roma pupils for remote learning during lockdown, the establishment of contact between teachers and Roma pupils in such period, and the collaboration of Roma pupils and their parents with schools. The article also provides a comparative perspective of the position of Roma and other pupils and draws attention to the possible long-term consequences of remote learning for Roma pupils.
Keywords: izobraževanje; izobraževanje na daljavo; pandemija covid 19; Romi; Slovenija